Anders als die Andern - Malakaj, Ervin (Queer Film Classics, 2023)
Released in 1919, Anders als die Andern ( Different from the Others ) stunned audiences with its straightforward depiction of queer love. Supporters celebrated the film's moving storyline, while conservative detractors succeeded in prohibiting public screenings. Banned and partially destroyed after the rise of Nazism, the film was lost until the 1970s and only about one-third of its original footage is preserved today. Directed by Richard Oswald and co-written by Oswald and the renowned sexologist Magnus Hirschfeld, Anders als die Andern is a remarkable artifact of cinema culture connected to the vibrant pre-Stonewall homosexual rights movement of early-twentieth-century Germany. The film makes a strong case for the normalization of homosexuality and for its decriminalization, but the central melodrama still finds its characters undone by their public outing. Ervin Malakaj sees the film's portrayal of the pain of living life queerly as generating a complex emotional identification in modern spectators, even those living in apparently friendlier circumstances. There is a strange comfort in knowing that we are not alone in our struggles, and Malakaj recuperates Anders als die Andern 's mournful cinema as an essential element of its endurance, treating the film's melancholia both as a valuable feeling in and of itself and as a springboard to engage in an intergenerational queer struggle. Over a century after the film's release, Anders als die Andern serves as a stark reminder of how hostile the world can be to queer people, but also as an object lesson in how to find sustenance and social connection in tragic narratives.